Melatonin and cortisol secretion profile in patients with pineal cyst before and after pineal cyst resection. (May 2017) - Májovský, Martin; Řezáčová, Lenka; Sumová, Alena; Pospíšilová, Lenka; Netuka, David; Bradáč, Ondřej; Beneš, Vladimír
Highlights: Serum melatonin, cortisol and glucose 24-h profiles in patients before and after a pineal cyst resection. Patients harbouring pineal cyst preserve the physiological secretion of the hormone melatonin. The pineal cyst resection equals pinealectomy. Cortisol secretion substantially increased in patients after the surgery. Abstract: A pineal cyst is a benign affection of the human pineal gland on the borderline between pathology and normality. Only a small percentage of patients present with symptoms and a surgical treatment is indicated in highly selected cases. A melatonin secretion in patients with a pineal cyst before and after a pineal cyst resection has not been studied yet and the effect of surgery on human metabolism is unknown. The present study examined melatonin, cortisol and blood glucose secretion profiles perioperatively in a surgical group of 4 patients. The control group was represented by 3 asymptomatic patients with a pineal cyst. For each patient, 24-h circadian secretion curves of melatonin, cortisol and glycemia were acquired. An analysis of melatonin profiles showed an expected diurnal pattern with the night peak in patients before the surgery and in the control group. In contrast, melatonin levels in patients after the surgery were at their minimum throughout the whole 24-h period. The cortisol secretion was substantially increased in patients after the surgery. Blood glucose sampling showed no statistically significant differences. Clinical results demonstrated statistically significant headache relief measured by Visual Analogue Scale in patients after the surgery. Despite the small number of examined patients, we can conclude that patients with a pineal cyst preserved the physiological secretion of the hormone melatonin while patients who underwent the pineal cyst resection experienced a loss of endogenous pineal melatonin production, which equated with pinealectomy. Surprisingly, cortisol secretion substantially increased in patients after the surgery.